2002
DOI: 10.1097/00006565-200212000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of nonurgent emergency department use in the first 3 months of life

Abstract: Maternal and economic factors affected nonurgent ED utilization. Other critical factors still need to be explored. Interventions focused on decreasing nonurgent ED use in early infancy should be targeted at patients with the identified risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
10

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 13 publications
2
49
0
10
Order By: Relevance
“…A recent study of full-term neonates discharged from a single newborn nursery in Ohio found that one third of all ED visits were made when the primary care physicians' offices were open and 58% of these ED visits were determined to be nonurgent. 59 Only 15% of all visits to the ED were referred by a primary care physician. Twenty-nine percent of physician-referred visits were determined to be nonurgent while 64% of the self-referred visits were nonurgent.…”
Section: Commentmentioning
confidence: 99%
“…A recent study of full-term neonates discharged from a single newborn nursery in Ohio found that one third of all ED visits were made when the primary care physicians' offices were open and 58% of these ED visits were determined to be nonurgent. 59 Only 15% of all visits to the ED were referred by a primary care physician. Twenty-nine percent of physician-referred visits were determined to be nonurgent while 64% of the self-referred visits were nonurgent.…”
Section: Commentmentioning
confidence: 99%
“…Néanmoins, nous observons que les motifs de consultations étaient assez proches des diagnostics finalement retenus. Plus de la moitié des visites (54,2 %) était liée à des motifs « non urgents » qui auraient pu être facilement gérés en externe [3,4,11]. Cela nécessiterait cependant un réaménage-ment de l'offre de soins qui, en France, ne garantit pas toujours une réponse adaptée aux attentes parentales (accès difficile aux consultations de médecine générale ou de pédia-trie de ville, permanence des soins non assurée en soirée ou le week-end.…”
Section: Discussionunclassified
“…É tude épidémiologique, rétrospective des dossiers informatiques des nouveau-nés ayant consulté au SAU pédiatrique du CHU de Saint-É tienne du 1 er janvier au 31 décembre 2011. Les 4 critères combinés (1) enfant non adressé par un professionnel de santé, (2) score de gravité G1, G2, ou G3 de notre échelle interne à l'accueil, (3) absence de réalisation d'examen complémentaire et (4) retour à domicile ont été retenus pour définir les consultations non urgentes. Résultats.…”
Section: Résuméunclassified
See 1 more Smart Citation
“…Several studies have shown a particular presentation pattern for pediatric patients using emergency departments (EDs); that is, children visit EDs more often during the evening and late night than at other hours. 7,8 The pattern may vary between weekdays and weekend days 7 because use of emergency facilities is naturally influenced by the availability or nonavailability of other health care providers. To the contrary, the diurnal pattern in the use of emergency facilities may have a kind of regularity.…”
mentioning
confidence: 99%